Hubungan Status Gizi dengan Kejadian Diare pada Balita di Wilayah Kerja Puskesmas Pangi - Afriyanto Dai; Bayu Budi Laksono (Politeknik Unggulan Kalimantan, 2026)
Diarrhea remains a major health problem among under-five children and contributes significantly to childhood morbidity, particularly in primary healthcare settings. Nutritional status plays an important role in children’s immune response to infectious diseases; however, the association between nutritional status and diarrhea incidence varies across settings. This study aimed to analyze the relationship between nutritional status and diarrhea incidence among under-five children in the working area of Puskesmas Pangi in 2024.This study employed a cross-sectional analytic design using secondary data at the village aggregate level. Data on nutritional status were obtained from the 2024 child growth monitoring records (BNBA) using weight-for-height (W/H) indicators, while data on diarrhea incidence were collected from the 2024 routine reporting records of Puskesmas Pangi. The study population consisted of 725 under-five children recorded in both data sources. Data analysis included univariate analysis and bivariate analysis using Spearman correlation with a significance level of α = 0.05. The results showed that the majority of under-five children had normal nutritional status based on the W/H indicator. Diarrhea cases among under-five children were reported in all villages within the study area, with varying numbers of cases. Spearman correlation analysis indicated a positive but weak-to-moderate association between the proportion of poor nutritional status and the proportion of diarrhea incidence; however, the association was not statistically significant (p > 0.05). In conclusion, nutritional status was not significantly associated with diarrhea incidence among under-five children at the village aggregate level in the working area of Puskesmas Pangi in 2024. Comprehensive diarrhea prevention efforts should consider other contributing factors beyond nutritional status, including environmental sanitation, access to clean water, and hygienic behavior.